(untitled) (Marketing Jurnali, 2025)
This article provides an in -depth analysis of Indonesiaʼs financial market, which operates under a dual financial system through the integration of alternative finance within the conventional financial structure. The primary focus is on a comparative asses sment of the role of Islamic and conventional banks in the national financial ecosystem, exploring the state of financing within the production and services sectors, investment mobilization, and the provision of various financial services. Furthermore, the paper discusses the potential avenues for utilizing Indonesiaʼs expertise in Islamic finance to address existing challenges in the advancement of Islamic finance in Uzbekistan.